Divine Initiative and Paul’s Theological Epistemology: From 1 Corinthians 1–2 to Romans 9–11 - Barnhill, Gregory M. (Journal for the study of Paul and his letters, 2020)
The focus of this article is the function of divine initiative in the structure of Paul’s theological epistemology. In two key passages, 1 Cor 1:26-31 and Rom 9:6-29, Paul deploys the language of “calling” to emphasize the concept of divine initiative, specifically highlighting God’s freedom to “call” whomever he wants, paying no regard to any status of the recipient of his gracious love. In both texts, Paul deploys the language of “calling” to shift the focus to the God who calls, and even though each section plays a different role in relation to its context, both emphasize that God’s initiative plays a key role in how one knows Paul’s God. In both Corinth and Rome, the communities to which Paul writes face a significant problem (among others): improper boasting. And the solution to improper boasting that Paul offers to both the Corinthian and Roman Christ-believers is epistemological in nature: it has to do with knowing Paul’s God and his plan for the world correctly. This essay aims to capture Paul’s theologizing in action on the specific matter of boasting and to demonstrate that these situations in Corinth and Rome call forth from Paul a similar strategy: to highlight God’s initiative in knowledge of the divine. Moreover, because the topics of “faith” and “justification” are usually deemed more central to Paul’s theology, the role of “knowledge” as such is an under-explored factor in Paul’s theologizing as a whole. But as an apocalyptic theologian and thinker, the idea of revelation and “knowledge” must be retained as a central theological concept in Paul’s theologizing. In other words, recovering the structure of Paul’s epistemology is a key task for understanding his gospel. Paul’s God is known because he makes himself known, definitively in the Christ-event and prior to all human movement toward this God.